Developing Video Tutorials Based on Canva Application with Basic Competencies to Make Digital Gamis Patterns - Ningrum, Febrianita Yulia; Nashikhah, Ma'rifatun; Yuniati, Mita; Kharnolis, Mein (PT. Riset Press International, 2025)
This research is motivated by the need to improve the effectiveness of learning, considering that there are still many teachers who in teaching and learning activities use learning media that can be further developed to be more interactive and interesting, such as handouts and PowerPoint. The purpose of this research is to: 1) determine the feasibility of Canva application-based video tutorials on the basic competencies of making digital gamis in class XII students of the Fashion Management Department of SMKN 2 Jombang, 2) determine the response of students to the development of Canva application-based video tutorials on the basic competencies of making digital gamis patterns in Class XII students of the Fashion Management Department of SMKN 2 Jombang, 3) determine the learning outcomes of Class XII students of the Fashion Management Department of SMKN 2 Jombang who use Canva application-based learning media on the basic competencies of making digital gamis patterns. In addition, the response of students showed a percentage of 84%. The results showed that the Canva application-based learning media met the validity criteria based on the assessment of material experts, media experts and linguists. Based on the trial use of the media in learning, students show high interest in learning and easily understand the material provided. The conclusion of this study is that learning media based on the canva application can improve students` understanding so that they do not experience difficulties in practicum learning.